Improving the Army planning, programming, budgeting, and execution system (PPBES) : the programming phase - Lewis, Leslie; Brown, Roger Allen, 1940-; Schrader, John Y.; Rand eBooks (Santa Monica, CA : RAND, 1999)
As part of a special assistance activity for the Director of the U.S. Army's Program Analysis and Evaluation Directorate (PA&E), the Arroyo Center participated in creating a new program development process and methodology. The principal objective in this work was to improve the Army's Program Objective Memorandum (POM) development process. The improvements were designed to (1) enhance the Army's ability to view the totality of its resources, (2) improve its resource decision process, and (3) justify those choices within the Army and to the external community, including the Office of the Secretary of Defense, the Chairman of the Joint Chiefs of Staff, and the Congress.
"Arroyo Center."
Includes bibliographical references (p. 89-90).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army -- Appropriations and expenditures; United States. -- Army -- Decision making; United States. -- Army -- Management; Program budgeting -- United States; Electronic books